Show and Tell Learning Method Based on the Discovery Learning Model: Creativity and Learning Outcomes at Primary School - Nur, Zahra; Mulyadi, Mulyadi; Nurdiansyah, Erwin (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Conventional and boring learning paradigms typically lead to low creativity and learning outcomes in Pancasila and Citizenship Education. Researchers at Primary School 126 Inpres Kariango, Maros Regency, found a new way to attract kids interested in civics. This study examines how the Discovery Learning-based Show and Tell learning technique influences fifth-grade students' creativity and learning at Primary School 126 Inpres Kariango. This research is an experimental quantitative study. The study included 30 fifth graders. Pretests and posttests measured learning outcomes, and observation sheets measured student inventiveness. To assess intervention efficacy, descriptive and inferential statistics were used, including normality, homogeneity, and t-tests. The findings found considerable improvements in all areas: (1) Teacher instruction improved from "Very Poor" (35%) to "Good" (70%). (2) Student participation skyrocketed to "Very Good" (90%) at the final meeting. (3) Students' creativity scores increased from 49.00 (less creative) to 83.67 (creative/very creative). (4) Average student learning outcomes rose from 52.57 to 82.47, with 93.4% reaching moderate to very high. The hypothesis test shows that this strategy boosts creativity and learning. In conclusion, the Discovery Learning-based Show and Tell method enhances student learning in the PPKn subject, fosters creativity, and enhances interaction. This study helps teachers apply student-centered learning practices. This study strengthens our knowledge of how communicative strategies and discovery models improve primary school critical and creative thinking.